Distribution of breast lesions diagnosed by cytology examination in symptomatic patients at Eritrean National Health Laboratory, Asmara, Eritrea: a retrospective study - Kidane Siele Embaye; Saud Mohammed Raja; Medhanie Haile Gebreyesus; Matiwos Araya Ghebrehiwet (BMC, 2020)
Abstract Background Fine needle aspiration cytology is a simple, relatively accurate, non-invasive, and cost-effective method of diagnosing most breast pathologies. To date, there is no sufficient data depicting the distribution of breast lesions detected by fine needle aspiration cytology in our healthcare setting. The aim of this study was to elucidate the general distribution of breast lesions diagnosed by cytology test at Eritrean National Health Laboratory. Methods This retrospective study was carried out on 905 symptomatic patients between the years 2013 and 2017 at Eritrean National Health Laboratory. Diagnosis was made by fine needle aspiration cytology in patients with palpable breast lump and in some patients direct smear was prepared from a nipple discharge. Statistical analysis was carried out using Statistical Package for the Social Sciences version 23. Results A total of 905 patients were included in the study, of whom 871 (96.24%) were females. The age range of patients was from 13 to 93 years with mean and standard deviation of 33 ± 14.9 years. Breast lump, occurring in 892 (98.56%), was the most frequent presenting symptom. Fibroadenoma and fibrocystic breast lesions were the most prevalent lesions accounting for approximately 40% and 15%, respectively. Malignant breast lesions were seen predominantly in females above the age of 40 years with the highest frequency observed in the age range between 51 and 60 years. Pearson Chi-squared test showed significant association between patients' age above 40 years and the risk of having a malignant breast lesion (p < 0.001). The highest number of benign and malignant breast lesions was documented in 2014 with little fluctuation elsewhere in the study period. Conclusion Fine needle aspiration cytology is a procedure of choice for preoperative diagnosis in breast lesions mainly in a resource-limited settings. Our study identified the occurrence of malignant breast lesions in young women, which is of a paramount public health concern. Of note, significant proportion of patients were late to seek medical attention. Therefore, enhancement of community awareness regarding breast disease and implementation of screening programs are necessary to ameliorate the morbidity and mortality associated with the disease.